The successful treatment of systemic toxic induced paraquat poisoning by skin absorption: case reports and a literature review - Wang, Jia-Wei (Int J Clin Exp Pathol, 2019)
Paraquat (PQ) poisoning is life-threatening, can cause acute organ damage, and has a high mortality. However, cases of skin absorption induced by PQ poisoning are rare. This report describes a case where PQ was absorbed by the patient’s skin, causing severe organ damage. Having accidentally touched PQ on his skin, the patient, whose skin festered, became damaged, red, and swollen, developed serious systemic toxic symptoms. The patient recovered after systemic treatment. Generally speaking, being poisoned by PQ through skin absorption is rare. By analyzing the reported PQ poisoning through skin absorption and by reviewing the relevant literature, this paper aims to explore successful treatments for PQ poisoning through skin absorption and to provide treatment guidance for physicians encountering such cases.